Adaptation of spineless cactus to semi-arid region of Paraíba state, Brazil. - Torres-Sales, Aldo; de Mello Viera Leite, Luiz; Pereira de Andrade, Alberício (Agronomía Mesoamericana, 2015)
The aim of this study was to evaluate the adaptation of two spineless cactus of the species Nopalea cochenillifera Salm Dyck (Miuda and Alagoas) under the environmental conditions of the semi-arid region in the tate of Paraiba, Brazil. An experimental randomized block design with five replications was used. The experiment was conducted under field conditions in São João do Cariri county, State of Paraiba, Brazil (7°22’45,1”S and 36°31’47,2”W), from August 2004 to May 2007. Every twenty-eight days the relative growth rate of cladodes height, length, width, and thickness were evaluated, as well as the number of cladodes per plant and the photosynthetic active area of cladodes and plant. The biomass accumulation per hectare was also measured at the end of the experimental period. One thousand days after planting, the cultivars did not differ in length and width of cladodes. The Alagoas cultivar showed greater thickness of cladode than the Miuda. The Miuda had a larger number of cladodes (p>0.05). There was no difference (p>0.05) in biomass accumulation between cultivars. In conclusion, both cultivars showed similar behavior in the environmental conditions of the semiarid region of the State of Paraiba, Brazil.